CHINA’S “TWO-FACED” STRATEGY IN SOUTH CHINA SEA DISPUTE: BETWEEN SOFT OR HARD POWER APPROACH? - Probo Darono Yakti (Journal of Peace, Development and Communication, 2022)
China’s active presence in the South China Sea revolves around soft power and hard power. In recent years, China launched the Belt and Road Initiative strategy as the embodiment of Beijing’s geo-economic ambitions in the Indo-Pacific by inviting countries to invest in infrastructure in the Asia Investment and Infrastructure Bank (AIIB) on the one hand. Meanwhile, on the other hand, China is taking a firm stance in the region by continuing the Nine-Dash Line claim with several unilateral military actions in securing the Spratly and Paracel Islands. This study uses a qualitative method of explanation in explaining the question: how is China’s “two-faced” strategy in its foreign policy in dealing with the South China Sea dispute? The literature review found a gap between China’s security policy and studies on the South China Sea, namely the two-faced strategy. This study uses a double standard foreign policy and also Joseph Nye’s smart power. With the concepts offered, this study can elaborate on the role of decision-makers in formulating Chinese security policies. Besides, it examines the different responses of the claimant and non-claiming countries in the South China Sea such as Brunei Darussalam, the Philippines, Indonesia, Malaysia, and Vietnam. In the end, this research resulted in the conclusion that China is using a “two-faced” strategy with a tendency to achieve two goals at once: geo-economic interests in BRI as well as demonstrating its existence in the Indo-Pacific region.